Rhodium(III)‐Catalyzed Regioselective Direct C‐2 Alkenylation of Indoles Assisted by the Removable N‐(2‐Pyrimidyl) Group. Issue 1 (13th January 2014) - Gong, Binwei; Shi, Jingjing; Wang, Xiaowei; Yan, Yunnan; Li, Qiu; Meng, Yanqiu; Xu, H. Eric; Yi, Wei
Abstract The C‐2‐alkenylindole unit is a key component of numerous natural products and pharmacophores. However, the intermolecular direct construction of the core structural motif remains challenging in organic synthesis. Here we report a new, efficient, and versatile methodology for the synthesis of C‐2‐alkenylindoles through rhodium(III)‐catalyzed direct CH functionalization of indoles with acrylates under air by employing a metal‐directing group strategy. This strategy gives a rare selectivity for the alkenylation N‐(2‐pyrimidyl)indoles at the C‐2 position and provides the functionalized C‐2‐ alkenylindoles under mild conditions with broad substrate tolerance. An expansion of the methodology has also been demonstrated to, for example, the direct alkenylation of pyrrole and facile deprotection of the pyrimidyl group. All the results suggest that this methodology could be served as a highly attractive alternative for the direct construction of biologically important C‐2‐alkenylindoles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>